Comparison of ilioinguial/iliohyphogastic nerves block with wound-infiltration on postoperative pain – a randomised controlled trial - Robyna Irshad Khan; Malika Hameed; Summaiya Ahsan Ali (Journal of the Pakistan Medical Association)
Objective: To compare postoperative pain scores at rest and on movement in patients undergoing open inguinal hernia repair between those receiving illioinguinal/illiohypogastric nerve block with ropivacaine or wound infiltration with ropivacaine.